2013
DOI: 10.1021/cg301674k
|View full text |Cite
|
Sign up to set email alerts
|

Long-Wavelength Photoluminescence from Stacked Layers of High-Quality Type-II GaSb/GaAs Quantum Rings

Abstract: We report the successful molecular-beam epitaxial growth of 10 stacked layers of GaSb/GaAs quantum rings using a new procedure. Exact control of the arsenic flux during capping helps to reduce the strong group-V As−Sb exchange reactions, enabling the rings to be capped at the same growth temperature (480 °C) without dissolution. X-ray diffraction and transmission electron microscopy indicate excellent structural quality and uniformity with no threading dislocations. This is due to the reduction in the average … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…These holes are believed to originate from unintentional background doping and act to increase the ground-state transition energy compared with an uncharged dot. Sample J has the lowest E 0 value reported for any GaSb/GaAs QD/QR sample 37 and, during growth, this sample was exposed to high temperatures for the longest time, due to the hot GaAs cap temperature and 10 layers of QR growth. It has been shown that higher temperature MBE growth of GaAs decreases the incorporation of unintentional p-dopants.…”
Section: Discussionmentioning
confidence: 96%
“…These holes are believed to originate from unintentional background doping and act to increase the ground-state transition energy compared with an uncharged dot. Sample J has the lowest E 0 value reported for any GaSb/GaAs QD/QR sample 37 and, during growth, this sample was exposed to high temperatures for the longest time, due to the hot GaAs cap temperature and 10 layers of QR growth. It has been shown that higher temperature MBE growth of GaAs decreases the incorporation of unintentional p-dopants.…”
Section: Discussionmentioning
confidence: 96%
“…For light generation purposes, however, the reduction in electron-hole overlap could be detrimental to operating performance. Fabrication of GaSb/GaAs nanostructures by molecular beam epitaxy (MBE) has been shown to result in the formation of nano-rings, [8][9][10] rather than dots, under specific growth conditions. GaSb quantum rings [ Fig.…”
mentioning
confidence: 99%
“…GaSb quantum rings [ Fig. 1(a)] have recently been studied in bulk optical measurements, [9][10][11][12] and found to have some surprising optical properties. Cross-sectional scanning tunnelling microscopy (x-STM) has revealed that the ring geometry can confine the electron's wavefunction in its centre, 13 as illustrated in the band diagram in Fig.…”
mentioning
confidence: 99%
“…Indeed, the growth of defect-free 10-fold stacks of GaSb/GaAs QRs has recently been demonstrated. 40 The disadvantage of QRs (compared to QDs) is that the reduction in volume due to their geometry increases the capacitive charging energy, and hence the amount of charge that can be stored: here we report a charging energy of 24 meV for MBE-grown GaSb QRs compared to 13 meV for GaAsSb QDs grown by MOCVD 17,41 . However, given that we are now considering GaSb nanostructures as a basis for SV-RAM, which implies a single bit per cell (programming of multi-bit cells is slow), it may be that only a few holes need to be stored, in which case capacitive charging energy becomes less important.…”
Section: Discussionmentioning
confidence: 69%